FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DI KANTOR KELURAHAN MELAYU KECAMATAN TENGGARONG - Farida Ariani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The aim of this research is to measure and to analyze the impact of capability variable, motivation variable and opportunity variable toward employee performance. In this article the writer uses the primary data obtained from 41 respondents. All of respondents are employees at Kelurahan Melayu, Kec. Tenggarong. The result asserts that those variables mentioned above have different impact toward employee performance.